2022
DOI: 10.3233/ppr-210622
|View full text |Cite
|
Sign up to set email alerts
|

SingStrong – singing for better lung health in pulmonary fibrosis: A feasibility study

Abstract: BACKGROUND & PURPOSE: Pulmonary fibrosis (PF) is a debilitating, incurable disease. Strategies to optimise health-related quality of life and minimise symptom impact are advocated. Available treatment options such as pulmonary rehabilitation have been severely disrupted due to COVID-19. This feasibility study explored the clinical efficacy and acceptability of an online singing and breathing retraining programme (SingStrong) for people with PF. METHODS: The weekly online programme conducted over 12 weeks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Most quantitative studies reported on an improvement in the participants in physical or psychosocial areas. Seven studies reported positive changes in both domains [17,18,21,23,26,40,41], and one study reported no change in either domain [16]. Among the studies that measured physical function, 16 out of the 17 reported positive changes in this area.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most quantitative studies reported on an improvement in the participants in physical or psychosocial areas. Seven studies reported positive changes in both domains [17,18,21,23,26,40,41], and one study reported no change in either domain [16]. Among the studies that measured physical function, 16 out of the 17 reported positive changes in this area.…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently conducted research method was randomized controlled trials (RCT) (n = 12) including one feasibility study [18] and two pilot studies [19,20]. Aside from RCT, there were five one-group pre-post design studies [21][22][23][24][25], three case studies [26][27][28] and descriptive studies including study protocols [29,30], and program evaluation [31,32]. Three qualitative studies were also found [33][34][35].…”
Section: Methodological Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…The benefits of structured singing programmes for lung health, which are offered outside the traditional health service model, are also emerging. 105 …”
Section: Standardmentioning
confidence: 99%